Fintech terhadap Kinerja Keuangan Perbankan Syariah di Indonesia - Muhamad Syahwildan; Tri Damayanti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to determine the effect of mobile banking, internet banking and sms banking on the financial performance of Islamic banking in Indonesia. The type of research used in this research is descriptive research with a qualitative approach. The population in this study are all financial reports published by Islamic banks that have used mobile banking, internet banking and sms banking, namely BRI Syariah, BNI Syariah, Syariah Mandiri, BCA Syariah, Bukopin Syariah and BJB Syariah and have reported their financial statements with a period of 2015-2020. The results showed that mobile banking, internet banking and sms banking had a significant effect on the financial performance of Islamic banks in Indonesia